2019
DOI: 10.1177/0145721719843680
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Risk Assessment, A1C Measurement, and Goal Achievement of Standards of Care in Adults Experiencing Homelessness

Abstract: The purpose of this study was to explore diabetes in adults experiencing homelessness by evaluating diabetes risk, A1C measurement, and achievement of the goals of the American Diabetes Association (ADA) Standards of Medical Care in Diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Few other studies have documented relatively high rates of inadequately managed diabetes among patients experiencing homelessness, including 32% (HbA1c > 8%) and 50% (A1c> 7·3%) compared with 20% among domiciled persons with diabetes, which were significant across ethnicity and race. 10 , 11 Considering the higher prevalence of other important risk factors for cardiovascular events such as inadequately managed hypertension, hyperlipidemia, and cigarette smoking among patients experiencing homelessness shown in our study and other literature, effective treatment and better diabetes management among patients experiencing homelessness gains even more importance. 19 , 20 …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Few other studies have documented relatively high rates of inadequately managed diabetes among patients experiencing homelessness, including 32% (HbA1c > 8%) and 50% (A1c> 7·3%) compared with 20% among domiciled persons with diabetes, which were significant across ethnicity and race. 10 , 11 Considering the higher prevalence of other important risk factors for cardiovascular events such as inadequately managed hypertension, hyperlipidemia, and cigarette smoking among patients experiencing homelessness shown in our study and other literature, effective treatment and better diabetes management among patients experiencing homelessness gains even more importance. 19 , 20 …”
Section: Discussionmentioning
confidence: 60%
“… 5 , 6 , 7 , 8 , 9 Diabetes management in persons experiencing homelessness has not been well-studied. 10 , 11 Persons experiencing homelessness with diabetes have a higher rate of emergency room visits and hospital admissions for diabetes complications than domiciled adults. 12 Persons experiencing homelessness experience mental illness or substance misuse, encounter discrimination and stigma within the healthcare system, and face barriers to accessing primary care and achieving therapeutic lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
“…PSH initiatives have helped secure and maintain stable housing and meet some of the residents' health care needs (Henwood et al, 2017;Rog et al, 2014). Yet research shows residents face ongoing challenges in trying to maintain healthy lifestyle habits to manage chronic conditions, leading to greater risk for increased complications (Hadenfeldt et al, 2019;Rog et al, 2014). A 2017 study of PSH adults in Los Angeles County found that 68% had two or more chronic physical health conditions, more than half experienced depression and about one third reported diagnoses of schizophrenia, bipolar disorder or post-traumatic stress disorder (Henwood et al, 2017).…”
Section: Yet Many Individuals In Psh (Residents Hereafter) Have Unmet Physicalmentioning
confidence: 99%
“…Yet, nurse participants noted that physical health concerns were important to residents and were difficult to treat in a timely manner. Research has shown that residents are challenged to maintain their health and properly manage their chronic conditions, and are at higher risk for developing complications (Hadenfeldt et al, 2019;Rog et al, 2014). One study of residents' health outcomes after 2 ½ years in PSH found that mental health improved but physical health remained unchanged (Hunter et al, 2017).…”
Section: Authenticity In Communication and Healthcare Planningmentioning
confidence: 99%